2016
DOI: 10.1007/s12195-016-0456-5
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Enrichment Impairs Capacitative Calcium Entry, eNOS Phosphorylation & Shear Stress-Induced NO Production

Abstract: Endothelial dysfunction, characterized by decreased production or availability of nitric oxide (NO), is widely believed to be the hallmark of early-stage atherosclerosis. In addition, hypercholesterolemia is considered a major risk factor for development of atherosclerosis and is associated with impaired flow-induced dilation. However, the mechanism by which elevated cholesterol levels leads to decreased production of NO is unclear. NO is released in response to shear stress and agonist-evoked changes in intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…These findings provide in vivo evidence for hypercholesterolemia‐induced suppression of eNOS, mostly mediated by the suppression of Kir channel activity. This is an effect that was previously reported in cultured aortic ECs loaded with cholesterol and exposed to shear stress . In addition, a decrease in Akt phosphorylation was previously reported in various hypercholesterolemic models …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings provide in vivo evidence for hypercholesterolemia‐induced suppression of eNOS, mostly mediated by the suppression of Kir channel activity. This is an effect that was previously reported in cultured aortic ECs loaded with cholesterol and exposed to shear stress . In addition, a decrease in Akt phosphorylation was previously reported in various hypercholesterolemic models …”
Section: Discussionsupporting
confidence: 82%
“…This is an effect that was previously reported in cultured aortic ECs loaded with cholesterol and exposed to shear stress. 52 In addition, a decrease in Akt phosphorylation was previously reported in various hypercholesterolemic models. [53][54][55] Another possible connection between inhibition of Kir activity and a decrease in the availability of NO is eNOS uncoupling via elevated production of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 83%
“…Andrews et al reported that the initiation of mechanotransduction in adult BMECs and fetal BMECs may be prevented by transformation into an immortalized D3 cell line. [ 260 ] It would be of interest to produce a series of thorough experiments by comparing and contrasting immortalized BMEC cell lines to the iPSC‐counterparts, in particular in regard to the use of shear stress as a barriergenic agent so as to establish within the BBB community preferred cell line.…”
Section: The Effect Of Fss On Bmecmentioning
confidence: 99%
“…It should be noted that apoptotic bodies (;800-5000 nm diameter) that are released from apoptotic cells exhibit ectosome characteristics but are rarely described in intracellular communication because they would be rapidly destroyed by phagocytes (87). Little is known about EVs derived from BMECs (12,85,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98). Secreted by BMECs, EVs are heterogeneous in size and include ectosomes (;150-1000 nm diameter) and exosomes (;20-150 nm diameter) (99,100).…”
Section: Modulation Of Bbb Function By Extracellular Hspmentioning
confidence: 99%